Fentanyl Exposure in Preterm Infants: Five-Year Neurodevelopmental and Socioemotional Assessment - Mills, Kimberly P.; Lean, Rachel E.; Smyser, Christopher D.; Inder, Terrie; Rogers, Cynthia; McPherson, Christopher C. (Frontiers in Pain Research, 2022)
Objective To evaluate the association between cumulative fentanyl dose during neonatal intensive care and 5-year neurodevelopmental and socioemotional outcomes in very preterm infants. Materials and Methods Patient demographics and clinical factors during the perinatal and neonatal course were collected in 84 patients born between 23- and 30-weeks gestational age (GA). Cumulative fentanyl dose during neonatal intensive care was calculated. Developmental testing at age 5 years included the Wechsler Preschool and Primary Scale of Intelligence Full-Scale Intelligence Quotient, Third Edition, Clinical Evaluation of Language Fundamentals-Preschool, Second Edition, Movement Assessment Battery for Children, Second Edition (MABC-2), and Shape School Assessment. Socioemotional outcomes were assessed via caregiver's responses on the Child Behavior Checklist/1.5-5 (CBCL/1.5-5.5) and Social Responsiveness Scale, Second Edition (SRS-2). Covariates were identified on bivariate analysis (p < 0.1). Linear regression models related outcome measures to the log of cumulative fentanyl dose adjusted for covariates. Results Higher cumulative fentanyl dose was associated with lower composite motor scores on bivariate analysis (p < 0.01). Cumulative fentanyl dose did not correlate with composite intelligence quotient, language, or executive function. The Clinical Risk Index for Babies score, log of mechanical ventilation, inotrope, and anesthesia duration, and log of cumulative midazolam and hydrocortisone dose were also associated with MABC-2 scores (p < 0.1). Cumulative fentanyl dose was not associated with composite MABC-2 scores on multiple linear regression. Higher cumulative fentanyl dose was associated with decreased socioemotional problems based on caregiver's response on CBCL/1.5-5.5 t-scores driven by fewer symptoms of depression. The McMaster Family Assessment Device general functioning scale score, maternal age, GA, log of total parenteral nutrition days, patent ductus arteriosus requiring treatment, and log of inotrope hours were also associated with CBCL/1.5-5.5 t-scores (p < 0.1). Cumulative fentanyl dose (p = 0.039) and family dysfunction score (p = 0.002) remained significant after controlling for covariates on multiple linear regression. Conclusion Cumulative fentanyl dose during neonatal intensive care did not correlate with 5-year motor, cognitive, or language outcomes after controlling for other variables. Fentanyl dose was associated with caregiver reported total socioemotional problems on the CBCL/1.5-5.5 on multivariate modeling. Additional long-term studies are needed to fully elucidate the safety of fentanyl in very preterm neonates.